2022
DOI: 10.1167/iovs.63.1.41
|View full text |Cite
|
Sign up to set email alerts
|

MiR-223-3p Regulates Autophagy and Inflammation by Targeting ATG16L1 in Fusarium solani–Induced Keratitis

Abstract: Purpose Increasing evidence suggested that microRNAs (miRs) are implicated in the regulation of the inflammatory response and autophagy in multiple diseases. The present study aimed to explore the effect of miR-223-3p on inflammation and autophagy in fungal keratitis (FK). Methods An FK mouse model was established, and primary corneal stromal cells were isolated by inoculation with Fusarium solani . The expression of miR-223-3p was determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…After activation of autophagy, corneal stromal cells are more activated and the clearance of fungus is accelerated, which is helpful for the repair of keratitis. 17 , 24 , 45 METTL3-mediated m6A methylation can negatively regulate autophagy, and downregulation of METTL3 can promote the expression of autophagy-related genes and enhance autophagy. 46 , 47 Therefore, we speculate that downregulation of METTL3 may promote fungal clearance by increasing autophagy flux, and further experimental validation is needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After activation of autophagy, corneal stromal cells are more activated and the clearance of fungus is accelerated, which is helpful for the repair of keratitis. 17 , 24 , 45 METTL3-mediated m6A methylation can negatively regulate autophagy, and downregulation of METTL3 can promote the expression of autophagy-related genes and enhance autophagy. 46 , 47 Therefore, we speculate that downregulation of METTL3 may promote fungal clearance by increasing autophagy flux, and further experimental validation is needed.…”
Section: Discussionmentioning
confidence: 99%
“…After 2 weeks, the FK models were established as described in our previous study. 17 In brief, intraperitoneal injection with 0.6% pentobarbital sodium was applied for general anesthesia, and 0.5% proparacaine hydrochloride was used for topical anesthesia in mice. Subsequently, the corneal epithelium (2.5 mm in diameter) was removed with an electric scraper.…”
Section: Methodsmentioning
confidence: 99%
“…Increased expression of tear miR-223-3p in HEK patients has also been reported in the corneal stromal cells of fungal keratitis murine models [ 57 ], associating it with keratitis pathophysiology. Studies have shown upregulation of miR-155 and miR-132 in association with HSV keratitis murine models, specifically in angiogenesis of the cornea [ 70 , 71 ].…”
Section: Herpes Epithelial Keratitismentioning
confidence: 96%
“…Furthermore, the miR-16, miR-142, and miR-223 families are crucial during hematopoietic lineage differentiation and are known to participate in the development and differentiation of immune cells [ 19 , 56 ]. Upregulation of miR-223-3p leads to increased detection of pro-inflammatory cytokines TNF-α and IL-1β in the corneas of mouse models of fungal keratitis [ 57 ]. Cortes-Troncoso et al found that miR-142-3p, which was expressed in the salivary glands of SS patients but not healthy controls, is transported from activated T-cells into glandular cells where it is capable of restricting cAMP production and altering intracellular Ca 2+ signaling [ 58 ].…”
Section: Sjögren’s Syndromementioning
confidence: 99%
“…As one of infectious corneal diseases, fungal keratitis may result in blindness [ 69 ]. In Fusarium solani fungal keratitis (FK) mouse models, miR-223-3p might regulate autophagy via targeting ATG16L1 and was associated with the inflammatory response, which might be a potential therapeutic target [ 70 ]. Another study has demonstrated that the expression of miR-665-3p in the cornea was upregulated and autophagy flux was impaired when infected with Fusarium solani, thus miR-665-3p inhibitors might activate autophagic pathways and inhibit inflammation to cure FK [ 71 ].…”
Section: Research Progress Of Exosomes and Autophagy In Ocular Surfac...mentioning
confidence: 99%